The Reverse Turn as a Polypeptide Conformation in Globular Proteins - Crawford, James L. (National Academy of Sciences, 1973)
The reverse turn, involving four consecutive amino acids, as a tertiary conformation in globular proteins is defined in terms of dihedral angles, the C(1)(α)...C(4)(α) distance and the O(1)...H-N(4) hydrogen bond distance. In seven proteins we find 125 examples of turns, comprising 33% of the amino acids in these proteins, as compared with 34% of the residues forming helices and only 17% forming β-sheets. The amino-acid compositions of turns, helices, and β-sheets are analyzed in some detail. We find Asn and Gly mainly in turns, Pro in turns (and at the beginning of helices), and Glu in helices. In these turns a statistical survey indicates that 19% of Asp residues are in the first position, 33% of Pro residues are in the second position, 24% of Asn residues are in the third position, and 26% of Trp residues are in the fourth position.